Targeting viral antigens to CD11c on dendritic cells induces retrovirus-specific T cell responses. - Asim Ejaz (Public Library of Science (PLoS), 2012)
Dendritic cells (DC) represent the most potent antigen presenting cells and induce efficient cytotoxic T lymphocyte (CTL) responses against viral infections. Targeting antigens (Ag) to receptors on DCs is a promising strategy to enhance antitumor and antiviral immune responses induced by DCs. Here, we investigated the potential of CD11c-specific single-chain fragments (scFv) fused to an immunodominant peptide of Friend retrovirus for induction of virus-specific T cell responses by DCs. In vitro CD11c-specific scFv selectively targeted viral antigens to DCs and thereby significantly improved the activation of virus-specific T cells. In vaccination experiments DCs loaded with viral Ag targeted to CD11c provided improved rejection of FV-derived tumors and efficiently primed virus-specific CTL responses after virus challenge. Since the induction of strong virus-specific T cell responses is critical in viral infections, CD11c targeted protein vaccines might provide means to enhance the cellular immune response to prophylactic or therapeutic levels.